Treatment of municipal solid wastes leachate by means of chemical- and electro-coagulation - Veli, Sevil; Ozturk, Tuba; Dimoglo, Anatoly (Elsevier, 2008)
In this study, treatment of municipal solid waste leachate (L1, L2) by means of chemical- and electro-coagulation (EC) methods was investigated. The removal of chemical oxygen demand (COD), total organic carbons (TOC) and color from leachate was experimentally investigated by using chemical- and electro-coagulation. Aluminum and iron were used simultaneously in the reactor as materials for electrodes. Percent of COD, TOC and color removal versus the electro-chemically generated Fe2+ and Al3+ doses are examined in this study. The best removal has been achieved in the COD parameter. Thus, in electro-coagulation method, the maximal removal is 87% for the L1 solution, while for L2 it is 90% for Fe2+ and 77% for L1 and 88% for L2 for Al3+ ion solutions. High color removal for Fe,21 is observed for L1 (86%), while for L2 it is approximately 99%. The removal indices for the leachate treatment by chemical coagulants (FeSO4 center dot 7H(2)O and Al-2(SO4)(3)center dot 18H(2)O) appeared to be lower than for the electrochemically generated Fe2+ and Al3+. The results show that electro-coagulation could be considered as an effective alternative solution for the treatment of leachate. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: leachate; chemical-coagulation; electro-coagulation; Al/Fe electrode; wastewater treatment